Method for modifying performance of sodium-ion battery at low cost
By physically mixing titanium nitride and tungsten oxide with O3 type NaNi1/3Fe1/3Mn1/3O2 positive electrode material, the problem of structural instability and insufficient performance of the material during the cycle is solved, and the performance improvement of sodium ion batteries is achieved and cost reduction.
Patent Information
- Application Number
- CN202411552372.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The O3-type NaNi1/3Fe1/3Mn1/3O2 cathode has problems such as structural instability, poor magnification and cycle stability during the cycle process, and the existing modification methods ignore the impact of cost, resulting in complex processes and high preparation costs.
By physically mixing titanium nitride and tungsten oxide with NaNi1/3Fe1/3Mn1/3O2 positive electrode active material, a modified sodium ion battery positive electrode material is prepared, using the electrical and thermal conductivity of titanium nitride and the high conductivity of tungsten oxide. and thermal stability, improving the cycle stability and electrochemical performance of the battery.
The performance improvement of the positive electrode material of sodium ion battery has been achieved, especially in terms of cycle stability and rate performance, and the simple physical mixing method is adopted, which reduces the preparation cost and is suitable for industrial production.
Smart Images

Figure CN119480925A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery optimization, and in particular relates to a method for providing a low-cost method for modifying the performance of a sodium ion battery. Background Art
[0002] At present, the rapid development of energy storage technology has become a key measure for human society to alleviate the dual pressures of energy consumption and environmental pollution. However, the uneven distribution and limited reserves of lithium resources have brought great challenges to the widespread application of lithium-ion batteries, especially large-scale energy storage applications. Therefore, there is an urgent need to develop high-energy-density, safe, and sustainable sodium-ion batteries. Among the existing SIBs positive electrode materials, O3-type layered NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (NaNFMO) has attracted much attention due to its easy synthesis, unique crystal structure and excellent electrochemical performance. The O3-type structure specifically refers to the sodium ions occupying the octahedral position and the oxygen ions forming a cubic close-packed structure, which provides a favorable channel for the insertion and removal of sodium ions. This structure enables the O3-type material to maintain high structural stability and ionic conductivity during the cycle, thereby achieving high energy density and cycle stability. However, the O3-type NaNFMO cathode also faces challenges. The sliding of the transition metal layer and the complex phase change during the cycle result in structural instability, poor rate and cycle stability. Traditional modification methods mainly involve element doping and surface coating during material synthesis. For example, Li et al. used the ion conductor Na3Zr2Si2PO 12 As a surface coating material, and by doping with Zr, the surface / interface side reactions and O3-P3 phase transitions were significantly alleviated (10.1016 / j.jechem.2021.12.018). Hong alleviated the unfavorable phase transition of P3-O3'-P3' by Sc doping, stabilized the layered structure, alleviated the formation of microcracks, and hindered the side reactions at the interface during long-term cycles (10.1002 / aenm.202302793). Deng showed through theoretical calculations that weakly solvated structures spontaneously form in low-concentration electrolytes, thereby promoting the desolvation process of Na+, and confirmed the construction of a dense and uniform cathode / electrolyte interface layer by time-of-flight secondary ion mass spectrometry (TOF-SIMS), which optimized the interface chemistry and improved the interface dynamics (10.1016 / j.ensm.2021.10.012). In addition, there are many modification methods, but they are undoubtedly all through improving Na + The material properties are improved by improving transport mechanics and improving interface compatibility. Although these methods effectively improve the performance of NaNFMO materials, they all ignore the impact of cost and have low commercial value for NaNFMO materials.
[0003] In view of the above situation, is there a low-cost and simple modification strategy at present? More than a decade ago, researchers have begun to study the application of adding highly conductive materials to positive electrode materials in lithium-ion batteries. For example, Hong et al. (10.1016 / j.cej.2020.126306) designed experiments to prove that low-cost TiN with excellent conductivity and high dielectric constant is not only conducive to electron transfer, but also promotes faster heat dissipation of the electrode during charging and discharging, which is conducive to achieving fast lithium ion diffusion kinetics, balanced CEI / SEI film evolution, and excellent cycle stability. The high localized dielectric polarization induced by TiN enhances the lithium ion dynamics around the three-phase interface of NCM523, TiN and electrolyte. Gao et al. (10.1016 / j.ensm.2024.103332) have made significant progress in achieving performance enhancement of NCM pouch batteries by introducing efficient trace dual additives: TiO2 and TiN. Specifically, a small amount of low-cost TiO2 and TiN additives were added to the NCM622 cathode electrode. The addition of these additives significantly improved the diffusion kinetics of lithium ions, enhanced the interfacial compatibility within the NCM622 graphite bag battery electrode, and effectively alleviated the electrode polarization. This area has also received attention in the field of sodium ion batteries. For example, Yeon et al. (10.1039 / c7ta08443a) used a simple dry ball milling process to coat Al2O3 nanoparticles to prepare surface-modified O3-type Na[Ni 0.6 Co 0.2 Mn 0.2 ]O2 cathode, which improves the half-cell cycle stability and rate performance, effectively reduces the side reaction with the electrolyte solution, and promotes Na + Migration. In addition, there are patent applications that further expand the application of adding highly conductive materials to positive electrode materials in the field of sodium batteries. For example, CN118156480A discloses a method for improving the performance of sodium ion batteries: using solid electrolytes and / or conductive agents to modify the sodium ion battery oxide positive electrode material by stirring and homogenizing: the prepared modified sodium ion battery oxide positive electrode material has good electrical conductivity, and the battery prepared using the modified sodium ion battery oxide positive electrode material has good cycle performance and first-cycle coulomb efficiency.
[0004] In summary, the application of conductive materials in the field of batteries is extensive. Although researchers have successfully achieved their respective goals through different strategies. Unfortunately, in the case of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 There are few studies on O2 materials. 1 / 3 Fe 1 / 3 Mn 1 / 3There are reports that high conductivity and high thermal conductivity materials are added to the O2 electrode modulation to improve the transport kinetics of sodium ions and improve its interfacial compatibility, and finally improve the performance of the whole battery. In addition, many studies have also ignored the impact of cost. Although these studies have enhanced the Na + The transport kinetics and side reactions are reduced, thus achieving excellent electrochemical performance. However, the process is relatively complicated, which increases the preparation cost to a certain extent and is not conducive to industrial production. Based on the above situation, it is very necessary to target NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 The development of a practical, simple, convenient and near-zero-cost macro-modification preparation strategy for O2 materials can improve the performance of the entire battery. Summary of the invention
[0005] In order to solve the O3 type NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 There are many problems with the O2 (NaNFMO) cathode during the cycle process. The purpose of the present invention is to provide a low-cost method for modifying the performance of sodium-ion batteries, which can prepare sodium-ion batteries with good comprehensive performance.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for modifying the performance of a sodium ion battery at a low cost comprises the following steps:
[0008] 1) The positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, titanium nitride and tungsten oxide are put into a mortar and mixed evenly to obtain a positive electrode modified material;
[0009] The mixing time in step 1) is 5 to 7 minutes.
[0010] 2) mixing the positive electrode modification material, the binder and the conductive agent to obtain a mixture, adding N-methylpyrrolidone, and mixing evenly to obtain a slurry;
[0011] 3) coating the slurry on a carbon-coated aluminum foil to form a sodium battery electrode;
[0012] 4) Drying the sodium battery pole pieces, cutting and assembling them to obtain sodium ion batteries.
[0013] Furthermore, in step 1), the weight percentage of each raw material is: titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2=1~3wt%: 1~3wt%: 94~98wt%.
[0014] Preferably, in step 1), the weight percentage of each raw material is: titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2=2wt%:3wt%:95wt%.
[0015] Furthermore, the mixing time in step 1) is 5 to 7 minutes.
[0016] Furthermore, the positive electrode modification material, adhesive and conductive agent described in step 2) are dried at 100-105° C. for 10-12 hours and then mixed.
[0017] Furthermore, when preparing button cells, the mass ratio of the positive electrode modifying material, the adhesive and the conductive agent in step 2) is 80:10:10, and the amount of N-methylpyrrolidone added is 50-60% of the mass of the slurry.
[0018] Furthermore, when preparing a soft-pack battery, the mass ratio of the positive electrode modifying material, the adhesive, and the conductive agent in step 2) is 94:3:3, and the added amount of the N-methylpyrrolidone is 50-60% of the mass of the slurry.
[0019] Furthermore, the binder in step 2) is polyvinylidene fluoride, and the conductive agent is carbon black.
[0020] Furthermore, the drying condition in step 4) is drying at 75-85° C. for 10-14 hours.
[0021] It should be noted that although the method of the present invention is based on NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is taken as an example, but the present invention is applicable to NaNi x Fe y Mn z Sodium nickel iron manganese oxide positive electrode active material for O2, wherein x+y+z=1, and the molar ratio Ni:Fe:Mn=1:1:1.
[0022] The present invention adopts the above technical scheme, firstly grinds titanium nitride, tungsten oxide and positive electrode active material in proportion to obtain positive electrode modified material, makes the prepared positive electrode modified material into slurry and then processes such as coating and sheet making to make positive electrode sodium battery pole sheet, that is, sodium ion battery positive electrode modified by titanium nitride and tungsten oxide particles, and then uses metal sodium sheet as negative electrode to assemble into sodium ion button battery; or, matches with negative electrode hard carbon to assemble into soft package full battery.
[0023] The present invention has the following advantages:
[0024] The present invention provides an efficient and convenient synthesis strategy for positive electrode materials for sodium ion batteries by adding metal nitrides and metal oxides in one step. Since titanium nitride has excellent electrical and thermal conductivity, its modified material can promote faster heat dissipation of the electrode during the charge and discharge process of the battery, which is conducive to achieving rapid sodium ion diffusion dynamics. Tungsten oxide has high electrical conductivity and good thermal stability. Its modified material can improve the interfacial compatibility and comprehensive electrical conductivity of the material, and can alleviate the transition metal dissolution of the active material and maintain the stability of the crystal structure. Under the joint action of titanium nitride and tungsten oxide, the performance of the positive electrode material of the sodium ion battery has been significantly improved, especially the cycle stability of the battery. In addition, the cost of titanium nitride and tungsten oxide is relatively low. The present invention adopts a simple physical mixing method to modify TiN and WO3 in NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, greatly improving the cycle life and electrochemical performance of sodium ion batteries. The electrode modification method is simple, low-cost, green and efficient. The full battery assembled with the electrodes prepared by the present invention has excellent rate performance and cycle performance, indicating the practicality of the modified electrode of the present invention. The present invention provides an industrially compatible strategy for improving the performance of NaNFMO batteries, which may provide some inspiration for the modulation of the sodium storage performance of other similar positive electrodes and their corresponding full batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 These are the XRD test results of the samples prepared in Examples 1, 2, 3 and 4 of the present invention.
[0026] Figure 2 The samples prepared in Examples 1, 2, 3 and 4 of the present invention were heated at 1C (1C = 115 mA g -1 ), charge and discharge cycle curves under 25℃ and 2.0-4.0V working conditions.
[0027] Figure 3 It is a battery rate performance diagram of 0.1-10C of samples prepared in Examples 1, 2, 3 and 4 of the present invention at 2.0-4.0V room temperature.
[0028] Figure 4 The samples prepared in Examples 1, 2, 3 and 4 of the present invention were heated to 1C (1C = 115 mAh g -1 ), charge and discharge cycle curves under 45℃ and 2.0-4.0V working conditions.
[0029] Figure 5 It is a battery rate performance diagram of samples prepared in Examples 1, 2, 3 and 4 of the present invention at 2.0-4.0V, 45°C and 0.1-20C.
[0030] Figure 6 It is the sodium ion diffusion coefficient curve of the samples prepared in Examples 1 and 4 of the present invention under the working conditions of 0.05C, 25°C, 2.0-4.0V and the constant current intermittent titration technique (GITT) during the charge and discharge process.
[0031] Figure 7 The charge and discharge cycle curves of the samples prepared in Examples 5 and 6 of the present invention made into a sodium ion soft-pack full battery with a capacity of 120 mAh at 25°C@2.0-4.0V. DETAILED DESCRIPTION
[0032] In order to make the technical solutions and advantages of the present invention more clear, the present invention is further described below in conjunction with specific implementation methods.
[0033] Preparation of positive electrode modified materials:
[0034] In a dehumidified room, titanium nitride and tungsten oxide were mixed with layered oxide positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2(NaNFMO) was uniformly mixed according to the following weight percentages, and then ground for 5 minutes to obtain a modified positive electrode material.
[0035] (1) Titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 = 2wt%: 0wt%: 98wt%, to obtain 2.0wt.% TiN modified NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode active material, denoted as NaNFMO-T.
[0036] (2) Titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 = 0wt%: 3wt%: 97wt%, to obtain 3.0wt.% WO3 modified NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode active material, denoted as NaNFMO-W.
[0037] (3) Titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 = 2wt%: 3wt%: 95wt%, resulting in 2.0wt.% TiN and 3.0wt.% WO3 modified NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 positive electrode active material, denoted as NaNFMO-TW.
[0038] Example 1
[0039] Weigh 0.02 g of polyvinylidene fluoride and disperse it in 0.3 g of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 0.16 g of NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 positive electrode active material and 0.02g Super P were mixed evenly to prepare slurry. The slurry was coated on carbon-coated aluminum foil to form a sodium battery pole piece. The sodium battery pole piece was dried and a button battery (recorded as sample 1) was obtained through a series of sodium ion battery processes such as cutting and assembly.
[0040] The electrolyte is a mixed solution of NaClO4 / DMC / EC / PC with a volume ratio of 1:1:1, NaClO4 is a conductive salt, and DMC (dimethyl carbonate) / EC (ethylene carbonate) / PC (propylene carbonate) is a composite solvent. A metal sodium sheet is used as the negative electrode, a glass fiber separator GF / F is used as the diaphragm, and nickel foam is used as the filler. The above sodium battery electrode is assembled into a button battery of model CR2025, with a capacity of 1C (1C = 115 mAh g -1 ) for charge and discharge, the charge and discharge voltage range is 2.0-4.0V, and the battery test results are listed in Table 1.
[0041] Example 2
[0042] Weigh 0.02 g of polyvinylidene fluoride and disperse it in 0.3 g of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 0.16 g of NaNFMO-T positive electrode active material and 0.02 g of Super P, mix well, and prepare slurry. Coat the slurry on carbon-coated aluminum foil to form a sodium battery pole piece. Dry the sodium battery pole piece, and obtain a button battery (recorded as sample 2) through a series of sodium ion battery processes such as cutting and assembly.
[0043] The battery electrodes, electrolyte, battery assembly and testing methods are the same as those in Example 1. The test results of the battery are listed in Table 1.
[0044] Example 3
[0045] Weigh 0.02 g of polyvinylidene fluoride and disperse it in 0.3 g of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 0.16 g of NaNFMO-W positive electrode active material and 0.02 g of Super P, mix well, and prepare slurry. Coat the slurry on carbon-coated aluminum foil to form a sodium battery pole piece. Dry the sodium battery pole piece, and obtain a button battery (recorded as sample 3) after a series of sodium ion battery processes such as cutting and assembly.
[0046] The battery electrodes, electrolyte, battery assembly and testing methods are the same as those in Example 1. The test results of the battery are listed in Table 1.
[0047] Example 4
[0048] Weigh 0.02 g of polyvinylidene fluoride and disperse it in 0.3 g of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 0.16 g of NaNFMO-TW positive electrode active material and 0.02 g of Super P, mix well, and prepare slurry. Coat the slurry on carbon-coated aluminum foil to form a sodium battery pole piece. Dry the sodium battery pole piece, and obtain a button battery (recorded as sample 4) through a series of sodium ion battery processes such as cutting and assembly.
[0049] The battery electrodes, electrolyte, battery assembly and testing methods are the same as those in Example 1. The test results of the battery are listed in Table 1.
[0050] Example 5
[0051] Weigh 0.3 grams of polyvinylidene fluoride and disperse it in 15 grams of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 9.4 grams of NaNFMO positive electrode active material and 0.3 grams of Super P, mix well, and prepare slurry. The slurry is coated on carbon-coated aluminum foil to form a positive electrode sheet of a sodium battery; weigh 0.2 grams of sodium carboxymethyl cellulose and disperse it in 15 grams of deionized water. After continuous dispersion at room temperature for 0.5 hours, add 9.3 grams of hard carbon negative electrode active material, 0.2 grams of Super P and 0.2 grams of styrene-butadiene rubber, mix well, and prepare slurry. The slurry is coated on copper foil to form a negative electrode sheet of a sodium battery. Then, after the preparation process of the bag-type full battery such as cutting the pole sheet, rolling the pole sheet, laminating, welding the pole ear, sealing the battery, injecting the electrolyte, battery formation and battery capacity division, the 383450 square soft pack battery (recorded as sample 5) was successfully assembled.
[0052] Among them, a mixed solution of 1molNaPF6 with a volume ratio of 100% DIGLYME is used as the electrolyte, NaPF6 is the conductive salt, and DIGLYME (diethylene glycol dimethyl ether) is the solvent. Under the condition of ambient temperature of 27±1℃, the charge and discharge test is carried out. First, the battery is charged with a constant current (NaNFMO||HC battery with a charge and discharge current of 60mA at 0.5C, the test current is 0.5C; the voltage is 4.0V), and then discharged (current size: 0.5C) to 1.5V, and data is collected.
[0053] Example 6
[0054] Weigh 0.3 grams of polyvinylidene fluoride and disperse it in 15 grams of N-methylpyrrolidone. After continuous dispersion at room temperature for 0.5 hours, add 9.4 grams of NaNFMO-TW positive electrode active material and 0.3 grams of Super P, mix well, and prepare slurry. The slurry is coated on carbon-coated aluminum foil to form a sodium battery pole piece; weigh 0.2 grams of sodium carboxymethyl cellulose and disperse it in 15 grams of deionized water. After continuous dispersion at room temperature for 0.5 hours, add 9.3 grams of hard carbon, negative electrode active material, 0.2 grams of Super P and 0.2 grams of styrene-butadiene rubber, mix well, and prepare slurry. The slurry is coated on copper foil to form a sodium battery negative electrode. Then, after the preparation process of the bag-type full battery such as cutting pole pieces, pole piece rolling, lamination, welding pole ears, sealing batteries, injecting electrolytes, battery formation and battery capacity division, the 383450 square soft pack battery (recorded as sample 6) was successfully assembled.
[0055] The battery electrodes, electrolyte, battery assembly and testing methods are the same as those in Example 5. The test results of the battery are listed in Table 2.
[0056] Table 1 Test results of Examples 1-4
[0057]
[0058] Table 2 Test results of Examples 5-6
[0059]
[0060] Figure 1 These are the XRD test results of samples 1, 2, 3 and 4. It can be found that the main peaks of TiN and WO3 are clear, and there are no other impurity peaks, and there is no effect on the crystal structure of the main material.
[0061] Figure 2 The cycling curves of samples 1, 2, 3 and 4 at 1C@2.0-4.0V at room temperature show that after 300 cycles of charge and discharge, the discharge capacity of sample 4 is 94.9mA g -1 The discharge capacity of sample 3 is 78 mA g -1 The discharge capacity of sample 2 is 70.9 mA g -1 , while sample 1 is only 59.9 mA g -1 , the capacity retention rates were 82.6%, 67.0%, 61.6% and 50.7% respectively.
[0062] Figure 3 The figure is the battery rate performance diagram of samples 1, 2, 3 and 4 at room temperature of 2.0-4.0V, and the rate capability in the range of 0.1 to 10C can be seen. As the current density increases, the reversible capacity of sample 1 decreases sharply, while sample 4 shows higher rate stability.
[0063] Figure 4 The following are the cycle curves of samples 1, 2, 3 and 4 at 45°C at 1C@2.0-4.0V. After 300 cycles of charge and discharge, sample 4 modified with titanium nitride and tungsten oxide still maintains a capacity retention rate of 70.1%, while sample 1 is only 43.8%, showing excellent high-temperature cycle stability.
[0064] Figure 5 The figure is the battery rate performance diagram of samples 1, 2, 3 and 4 at 2.0-4.0V and 45°C, and the rate capability in the range of 0.1 to 20°C can be seen. As the current density increases, the reversible capacity of sample 1 decreases sharply, while sample 4 shows higher rate stability at high temperature.
[0065] Figure 6 The sodium ion diffusion coefficient curves of samples 1 and 4 during the constant current intermittent titration technique (GITT) and the charge and discharge process at a current density of 0.05C show that the sodium ion diffusion rate of sample 4 is 4.03×10 -9 cm 2 s -1 , while the diffusion rate of sample 1 is only 9.00×10 -10 cm 2 s -1 , indicating that electrode modification can improve the ion diffusion rate of active substances.
[0066] Figure 7 The charge and discharge cycle curves of the sodium ion soft-pack full battery with a capacity of 120mAh made of samples 5 and 6 under 0.5C@2.0-4.0V conditions can be obtained from the results. After 300 cycles, the capacity retention rate of sample 6 is 58.2%, while that of sample 5 is only 46.1%, which further evaluates the practical application performance of the material and shows that TiN and WO3 modified NaNi 1 / 3 Fe 1 / 3Mn 1 / 3 The sodium ion positive electrode material of O2 has good application prospects for commercial production.
[0067] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for modifying the performance of sodium ion batteries at low cost, characterized in that: The following steps are involved: 1) The positive electrode active material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, titanium nitride and tungsten oxide are put into a mortar and mixed evenly to obtain a positive electrode modified material; 2) The positive electrode modification material, the binder and the conductive agent are mixed to obtain a mixture, and N-methylpyrrolidone is added thereto, and the mixture is mixed evenly to obtain a slurry; 3) coating the slurry on carbon-coated aluminum foil to form a sodium battery electrode; 4) Dry the sodium battery electrodes, cut them into pieces, and assemble them to obtain sodium-ion batteries.
2. A method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: The weight percentage of each raw material in step 1) is: titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2=1~3 wt% :1~3 wt% : 94~98 wt% .
3. A method for improving the performance of a sodium ion battery at low cost according to claim 2, characterized in that: The weight percentage of each raw material in step 1) is: titanium nitride: tungsten oxide: NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2=2 wt% :3 wt% : 95 wt% .
4. A method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: The mixing time in step 1) is 5 to 7 minutes.
5. The method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: Step 2) The positive electrode modification material, adhesive and conductive agent are dried at 100-105° C. for 10-12 h and then mixed.
6. The method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: When preparing button cells, the mass ratio of the positive electrode modification material, the adhesive and the conductive agent in step 2) is 80:10:10, and the amount of N-methylpyrrolidone added is 50-60% of the mass of the slurry.
7. A method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: When preparing a soft-pack battery, the mass ratio of the positive electrode modification material, the adhesive, and the conductive agent in step 2) is 94:3:3, and the added amount of the N-methylpyrrolidone is 50-60% of the slurry mass.
8. The method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: The binder in step 2) is polyvinylidene fluoride, and the conductive agent is carbon black.
9. The method for improving the performance of a sodium ion battery at low cost according to claim 1, characterized in that: The drying condition in step 4) is drying at 75-85° C. for 10-14 hours.
Citation Information
Patent Citations
O3-type nickel-iron-manganese-based sodium battery positive electrode material and preparation method thereof
CN117936748A